Development and application of tetrameric microsatellite markers for parentage identification in Pseudobagrus vachellii - Huan Wang; Feiyu Hu; Huaxing Zhou; Yuting Hu; Amei Liu; Guoqing Duan (Aquaculture Reports)
Pseudobagrus vachellii is an economically significant freshwater fish species in China. In this study, we identified 1,317,233 simple sequence repeats (SSRs) through whole genome resequencing and developed 20 tetrameric microsatellite markers for population genetic analysis. These markers exhibited high genetic diversity, with a mean allelic richness of 5.60 per locus. The observed and expected heterozygosity both exhibited relatively high levels, with average values of 0.650 and 0.602, respectively. Notably, 70 % of the loci (14/20) showed high polymorphism (PIC > 0.5). For parentage identification system development, we selected 13 highly polymorphic loci and optimized them into four multiplex PCR panels, balancing exclusion rates, locus number, assignment accuracy, and cost-time efficiency in genotyping. Additionally, SSR sequencing and genotyping were conducted on the validation population with known pedigree information using these panels. Subsequent genetic analyses, including gene frequency statistics, simulation analysis, and parentage identification, were performed using Cervus. The parentage analysis system demonstrated exceptional performance, with combined exclusion probabilities reaching 99.48 % for the first parent (CE-1P) and 99.99 % for both the second parent (CE-2P) and parent pair (CE-PP). Simulation analyses confirmed 100 % assignment accuracy, while practical application achieved 98.95 % correct parent-offspring assignments. This study not only expands the molecular marker resources for P. vachellii but also establishes a robust, efficient tool for parentage analysis in research and breeding programs.